The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1007/s000180050103
|View full text |Cite
|
Sign up to set email alerts
|

Psychrophilic enzymes: molecular basis of cold adaptation

Abstract: Abstract. Psychrophilic organisms have successfully provides enhanced abilities to undergo conformational colonized polar and alpine regions and are able to grow changes during catalysis. Thermal instability of coldefficiently at sub-zero temperatures. At the enzymatic adapted enzymes is therefore regarded as a consequence level, such organisms have to cope with the reduction of of their conformational flexibility. A survey of the psychrophilic enzymes studied so far reveals only minor chemical reaction rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
233
2
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(267 citation statements)
references
References 75 publications
23
233
2
4
Order By: Relevance
“…Life at low temperatures requires that psychrophilic organisms maintain sufficiently high metabolic fluxes despite thermal inhibition of enzyme reaction rates. In the case of intracellular enzymes, adaptation to cold can be achieved either by increasing k cat, or reducing K m , or both (39). This assumption is confirmed in the case of the psychrophilic PGK which adjusts both k cat and K m parameters, leading to a 2-fold improved catalytic efficiency with respect to the mesophilic PGK at 25°C.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Life at low temperatures requires that psychrophilic organisms maintain sufficiently high metabolic fluxes despite thermal inhibition of enzyme reaction rates. In the case of intracellular enzymes, adaptation to cold can be achieved either by increasing k cat, or reducing K m , or both (39). This assumption is confirmed in the case of the psychrophilic PGK which adjusts both k cat and K m parameters, leading to a 2-fold improved catalytic efficiency with respect to the mesophilic PGK at 25°C.…”
Section: Resultsmentioning
confidence: 73%
“…3) from psychrophilic to thermophilic PGK strongly suggest their involvement in temperature adaptation by modulation of the external shell compactness. In addition, it is known that the extremities of a protein are preferential sites for denaturation (20,39). In T. maritima and B. stearothermophilus PGK the N and C termini are linked by two salt bridges (D2-K397 and K3-E387, T. maritima PGK numbering) whereas only one connects the extremities of the mesophilic enzymes (K5-E413 in yeast).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that when the medium temperature decreases from 37 to 0°C, the enzymatic reaction rates can be reduced by 30-to 80-fold (Lonhienne, Gerday, & Feller, 2000). In order to cope with the reduction in chemical reaction rates and further to maintain sufficient metabolic fluxes, enzymes produced by psychrophiles generally feature a higher catalytic efficiency (K cat /K m ) at low temperatures than their warm-active counterparts (Feller & Gerday, 1997). The main strategy adopted by the psychrophilic enzymes to adapt to cold environments is believed to be their high intrinsic structural flexibility (Feller & Gerday, 1997;Lonhienne et al, 2000;Zecchinon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In order to cope with the reduction in chemical reaction rates and further to maintain sufficient metabolic fluxes, enzymes produced by psychrophiles generally feature a higher catalytic efficiency (K cat /K m ) at low temperatures than their warm-active counterparts (Feller & Gerday, 1997). The main strategy adopted by the psychrophilic enzymes to adapt to cold environments is believed to be their high intrinsic structural flexibility (Feller & Gerday, 1997;Lonhienne et al, 2000;Zecchinon et al, 2001). An increase in the structural flexibility can reduce the activation free energy which has to be overcome to reach the reaction intermediates, thus leading to a more efficient substrate turnover (Georlette et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Psychrophilic bacteria have been compared with mesophilic bacteria to provide clues for cold-adaptation. 1 The potential importance of molecular chaperones in efficient folding processes has been addressed for subzero temperatures.…”
Section: Introductionmentioning
confidence: 99%